2018
DOI: 10.1039/c7nr07035g
|View full text |Cite
|
Sign up to set email alerts
|

Nano-confinement-driven enhanced magnetic relaxivity of SPIONs for targeted tumor bioimaging

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are highly biocompatible and have a versatile synthetic technique based on coprecipitation, reduction-precipitation, and hydrothermal methods, where Fe and Fe react in aqueous solutions; both these ions are present in our body and have clear metabolic pathways; therefore, they have attracted extensive research interest and development in the field of diagnostic imaging and therapy. However, most SPION-based clinical diagnostic contrast agents are discontinued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…This study shed light on interpreting the relationship between the T 2 relaxivity and the magnetic field inhomogeneity induced by MNPs, especially in MNP clusters. [193][194] Previously, Mikhaylov et al reported that ferri-liposomes consisting of spherical IO NPs with widely dispersed diameters (i.e., ranging from 3 to 14 nm) exhibited ultrahigh r 2 value up to 1286 mM −1 s −1 by an unknown mechanism. [195] We speculate that this result may be a consequence of enhanced magnetic field inhomogeneity derived from the large size deviations of IO NPs used for fabricating the ferri-liposomes.…”
Section: Magnetic Field Inhomogeneitymentioning
confidence: 99%
“…This study shed light on interpreting the relationship between the T 2 relaxivity and the magnetic field inhomogeneity induced by MNPs, especially in MNP clusters. [193][194] Previously, Mikhaylov et al reported that ferri-liposomes consisting of spherical IO NPs with widely dispersed diameters (i.e., ranging from 3 to 14 nm) exhibited ultrahigh r 2 value up to 1286 mM −1 s −1 by an unknown mechanism. [195] We speculate that this result may be a consequence of enhanced magnetic field inhomogeneity derived from the large size deviations of IO NPs used for fabricating the ferri-liposomes.…”
Section: Magnetic Field Inhomogeneitymentioning
confidence: 99%
“…Similar effects have been noted in loading a high level of ultra-small SPIONs within polymeric nanoparticles. 36 However, this work represents the first example, to the best of our knowledge, of a paramagnetic contrast agent where Curie spin relaxation and outer-sphere effects dominate. This study not only illustrates the distinct mechanistic aspects of Dy-based agents, but also provides a general strategy to efficiently improve the r2 relaxivity under high field.…”
mentioning
confidence: 94%
“…Among the contrast agents, MRI CAs are safer when compared to those used in X-ray/CT scans and nuclear medicine. The commonly used CAs in Ce-MRI includes Gd 3+ , Mn 2+ , and Fe 3+ complexes Thanh Nguyen, Pitchaimani, Ferrel, Thakkar, & Aryal, 2018;Wahsner et al, 2018;Wang et al, 2018). Among these CAs, the majority of Ce-MRI is attributed to GBCAs due to their bright contrast due to its high magnetic moment, better thermodynamic, and kinetic stability in-vivo (Gizzatov et al, 2014;Schroeder, Clarke, Neubauer, & Tyler, 2011).…”
Section: Introductionmentioning
confidence: 99%